Pengaruh Budaya Organisasi terhadap Kepuasan Kerja Karyawan Tenaga Non Kesehatan di Unit Pelaksana Teknis Rumah Sakit Pratama Kota Yogyakarta - Muhammad Isnaini Fathoni; Mursyid, Mursyid (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2022)
This study aims to determine the effect of organizational culture on job satisfaction of non-health workers in the Technical Implementation Unit of the Yogyakarta City Pratama Hospital.The population in this study amounted to 67 people, while the sample in this study amounted to 57 people. The results of this study indicate that the magnitude of the Influence of Organizational Culture on Job Satisfaction of Non-Health Workers Employees in the Technical Implementation Unit of the Pratama Hospital, Yogyakarta City is 0,718.